KARAKTERISTIK KEPEMIMPINAN NABI MUSA DALAM AL-QUR’AN - Ismail, M. Ilyas; Tang, Ambo (Idaarah: Jurnal Manajemen Pendidikan, 2021)
Abstract: Characteristics of the Leadership of the Prophet Musa in the Qur’an The leadership characteristics of the prophet Musa are described in the Qur’an in detail and become a relevant leadership concept for leaders across generations and ages. The story of the prophet Musa dominates the love-stories in the al-Qur’an, shows the features of the life journey of a Moses and becomes an inspiration and consolation for anyone in living the wheel of life. Among the characteristics of his leadership are that: he has a strong determination and a strong sense of optimism in facing challenges; he has excellent physical strength to support all his activities as a leader and apostle of Allah to his people, the Children of Israel; having a big heart and receiving input and views from others is one of the characters shown by the prophet Musa; the prophet Moses showed social care and a willingness to help others; establish communication with anyone so that the vision and mission can be achieved; and the prophet Musa always improves spiritual and intellectual intelligence. Keywords: Characteristics, Leadership, Optimism, Intelligence Abstrak: Karakteristik Kepemimpinan Nabi Musa dalam al-Qur’an Ciri-ciri kepemimpinan Nabi Musa dijelaskan dalam al-Qur’an secara detail dan menjadi konsep kepemimpinan yang relevan bagi para pemimpin lintas generasi dan zaman. Kisah Nabi Musa mendominasi kisah-kisah cinta dalam al-Qur’an, memperlihatkan ciri-ciri perjalanan hidup seorang Nabi Musa dan menjadi inspirasi dan penghibur bagi siapa saja dalam menjalani roda kehidupan. Di antara ciri-ciri kepemimpinannya adalah: memiliki tekad dan rasa optimis yang kuat dalam menghadapi tantangan; memiliki kekuatan fisik yang prima untuk mendukung segala aktivitasnya sebagai pemimpin dan rasul Allah kepada umatnya, Bani Israil; memiliki hati yang besar dan menerima masukan serta pandangan dari orang lain; menunjukkan kepedulian sosial dan kemauan untuk membantu sesama; menjalin komunikasi dengan siapa pun sehingga visi dan misi dapat tercapai; dan selalu meningkatkan kecerdasan spiritual dan intelektual. Kata Kunci: Karakteristik, Kepemimpinan, Optimisme, Kecerdasan